1984
DOI: 10.1007/bf00433388
|View full text |Cite
|
Sign up to set email alerts
|

Precision of ventilatory and gas exchange alterations as a predictor of the anaerobic threshold

Abstract: Anaerobic threshold has been defined as the oxygen uptake (VO2) at which blood lactate (La) begins to rise systematically during graded exercise (Davis et al. 1982). It has become common practice in the literature to estimate the anaerobic threshold by using ventilatory and/or gas exchange alterations. However, confusion exists as to the validity of this practice. The purpose of this study was to examine the precision with which ventilatory and gas exchange techniques for determining anaerobic threshold predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

1986
1986
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 14 publications
0
23
0
2
Order By: Relevance
“…On the day of the data collection run, subjects warmed up for 5 min running at a freely chosen speed. After the warm-up, the 1-h run began with treadmill running at the predetermined speed and continued with a 5-min stage of unmonitored running allowing sufficient time to reach a stable oxygen uptake and providing some accommodation time to treadmill running (Candau et al 1998;Costill 1967;Powers et al 1984). Following the first 5 min, runners completed a stage including 2-min segments of running at their preferred stride frequency (PSF), then 4 and 8% above and below PSF.…”
Section: Methodsmentioning
confidence: 99%
“…On the day of the data collection run, subjects warmed up for 5 min running at a freely chosen speed. After the warm-up, the 1-h run began with treadmill running at the predetermined speed and continued with a 5-min stage of unmonitored running allowing sufficient time to reach a stable oxygen uptake and providing some accommodation time to treadmill running (Candau et al 1998;Costill 1967;Powers et al 1984). Following the first 5 min, runners completed a stage including 2-min segments of running at their preferred stride frequency (PSF), then 4 and 8% above and below PSF.…”
Section: Methodsmentioning
confidence: 99%
“…The ratio of the anaerobic threshold to the maximal oxygen consumption has been described as 50-60% in normal subjects 14,15,18) and approximately 70% in cardiac patients. 19,20) Previous reports have demonstrated that the anaerobic threshold was an accurate and reproducible index to classify the severity of an impairment of cardiac function.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, there have been several studies wherein VT is not always consistent with LT (GREEN et al, 1983;SIMoN et al, 1983;POWERS et al, 1984;GLADDEN et al, 1985), and which are negative about the cause-effect relationship between LT and VT (HAGBERG et al, 1982;HUGHES et al, 1982). Only two studies (GREEN et al, 1983;GLADDEN et al, 1985) reported a disassociation of LT and VT, using the objective method for determining both LT and VT. GREEN et al (1983) showed that VT occurred at a significantly higher work rate than LT, and GLADDEN et al (1985) showed that agreement between both was poor (r=0.29).…”
Section: Methodsmentioning
confidence: 99%